STABILITY AND ADAPTABILITY OF CARIOCA BEAN LINES AND CULTIVARS - ELIAS, Haroldo Tavares; BACKES, Rogério Luiz; VIDIGAL, Maria Celeste Gonçalves; BALBINOT JR., Alvadi Antonio; HEMP, Silmar (Scientia Agraria, 2007)
The common bean has been cultivated under different environmental conditions and technology levels. These environmental variations, linked to genotypes differences and interaction between genotypes and environments are the main reasons for those yield variations. The interaction genotype by environments has been a challenge for indication of cultivars and to select lines in breeding programs as well. The objective of this work was to evaluate the stability and adaptability of grain yield in 14 genotypes of carioca bean, studied in ten experiments of Cultivate Value and Using, carried out during agricultural years of 2000/01 and 2001/02. The experimental design utilized was the randomized blocks with four repetitions. The stability and adaptability were evaluated by non-parametric, bi-segmented and simple linear regression methodologies. The results demonstrated a concordance among methodologies for genotypes indications with exception for recommendation in unfavorable environments. The ideal genotype was not found by bi-segmented linear regression. The lines Vi 4899, Vi 0699 and Vi 4599 showed adaptability to general environments, and with LP 97-28 were indicated to unfavorable environments. In favorable environments Vi 4899, FT 97-155 and FTS Magnífico showed the better performances.